Social and economic dimensions leading to women committing moral crimes A theoretical sociological study - شحادة رمضان; نبال الجوراني (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The cohesion of society and the achievement of security and stability in it is a basic requirement for every society. For this reason, the phenomenon of crime has received great attention from researchers in the social sciences. In this study, we will address the most important social and economic variables and factors that lead to women committing a moral crime, and what are the conditions and factors leading to this deviant behaviorIn addition to knowing the impact of the crime on the criminalized woman socially, economically, and psychologically, in an attempt to reach a set of results and recommendations that would mitigate this dangerous phenomenon that is alien to society and that stands as an obstacle to its development and social, economic and family stability.